Two cases of multiple subcutaneous cystic phaeohyphomycosis in immunocompromised patients with a rare causative organism - Karkuzhali Ponnuswamy; Yogambal Muthureddy; Karthik Sigamani (Wolters Kluwer Medknow Publications, 2014)
Phaeohyphomycosis comprises a spectrum of mycotic infectious diseases caused by heterogeneous group of phaeoid fungi. A subcutaneous cystic swelling with histological hallmark of pigmented hyphae in tissues accompanied by pyogenic granuloma is diagnostic of phaeohyphomycosis. We present two cases of phaeohyphomycosis in 65- and 55-year-old male agriculturalists, who presented with multiple, cystic soft-tissue masses involving extremities. Culture was done in one case and the specific organism was identified as Aureobasidium pullulans.